Penerapan Algoritma C4.5 Dalam Klasifikasi Kualitas Sayur Kol Di Kabupaten Simalungun - Mhd Wendico Herdian; Riki Winanjaya; Susiani (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2022)
Cabbage is an annual plant or more in the form of a shrub. One of the centers for cabbage production is in Simalungun Regency, Ancient District. Cabbage has good demand prospects. However, erratic weather factors and plant pests that threaten to make the quality of cabbage vegetables are not good so that the impact on farmers' income is uncertain. In determining the appropriate and unfeasible cabbage, the Datamining Method with the C4.5 Algorithm is used. The C4.5 algorithm can provide a decision tree that is easy to interpret and has good accuracy so that the results obtained are expected to be input and help the agricultural office and farmers to determine the quality of cabbage vegetables that are good according to the target market. Become a reference for further research related to the users of the C4.5 Algorithm.